IMPLEMENTASI TEKNIK SUPERVISI AKADEMIK KEPALA SEKOLAH TERHADAP TENAGA PENDIDIK SEKOLAH DASAR UNTUK MENGHADAPI ERA DIGITAL - Desi Ratnasari; Roemintoyo Roemintoyo; Winarno Winarno (Universitas Negeri Malang, 2018)
Supervision is part of school-based management. Academic supervision conducted by school principals on teaching staff is very important to know the shortcomings and advantages of teaching staff in teaching. Several academic supervision techniques can be used in the implementation of supervision. This study aims to determine the implementation of the principal’s academic supervision techniques for teaching staff to deal with the digital era. This study uses a qualitative approach. Data collection techniques used are observation, interviews and documentation. This research was conducted in SD Negeri 02 Jetis, Jaten sub-district, Karanganyar district. The results of this study were principals using the academic supervision techniques of classroom visits, where the principal observed directly the classroom learning activities. Then the principal uses personal meeting techniques while providing guidance to educators. The competence of principals is needed in carrying out supervision techniques of educators because supervision techniques are very diverse and can be implemented in accordance with the conditions in each school.